Polytetrafluoroethylene fiber ptfe dust removal filter bag
By integrating nano Al2O3 particles with PTFE membranes and glass fiber-nano SiO2 composites, the PTFE filter bags address mechanical weaknesses and durability issues, offering superior performance and longevity in industrial dust filtration.
Patent Information
- Application Number
- CN202510155326.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-12
AI Technical Summary
Existing polytetrafluoroethylene (PTFE) dust filters suffer from mechanical weakness, poor durability, and short lifespan due to their unique molecular structure, which makes them difficult to process and limits their effectiveness in industrial dust filtration.
A modified PTFE fiber filter bag is created by loading nano Al2O3 particles onto PTFE membranes and combining them with a glass fiber-nano SiO2-PTFE composite fabric, enhancing mechanical strength and chemical stability through a needle-punching process.
The modified filter bags exhibit improved mechanical strength, chemical resistance, and extended lifespan, with enhanced hydrophobic and oleophobic properties, reducing clogging and extending filter life to over three years in high-temperature industrial environments.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dust removal filter bags, in particular to a polytetrafluoroethylene fiber PTFE dust removal filter bag. Background Art
[0002] In cement, steel, chemical, waste incineration and other industries, bag dust collectors have been widely used in industry, mainly for the treatment of flue gas and dust emitted in industrial production or in the surrounding environment, removing environmental pollution and purifying the air, which plays a positive and effective role. There are two main categories of existing dust filter bags: one is woven fabric, and the other is non-woven fabric. Woven fabric is interwoven by warp and weft yarns, with a relatively tight structure, high strength and durability, while needle-punched fabric entangles the fibers together through the up and down movement of the needles to form a fluffy and porous structure with good air permeability and good filtering performance. Among them, the dust filter bags obtained by the needle-punching process are more widely used.
[0003] The work of bag filter mainly relies on the filter bag of the bag filter to filter smoke and dust, and the filter material of the filter bag of the bag filter determines the adaptability of the filter bag of the bag filter to various smoke and dust, as well as the service life. Due to the complex environment of smoke filtration, the filter material must have the properties of corrosion resistance, high temperature resistance, oxidation resistance, and hydrolysis resistance. There are significant differences in the performance of fibers used for industrial filter materials. Commonly used high-temperature resistant filter materials are mainly polyphenylene sulfide (PPS) fiber needle felt, polyimide (P84) fiber needle felt, polytetrafluoroethylene (PTFE) fiber needle felt, glass fiber filter material, etc. Among them, polytetrafluoroethylene fiber has the characteristics of high temperature resistance, acid and alkali corrosion resistance, strong oxidation resistance, and no hydrolysis. Compared with the above-mentioned high temperature resistant fibers, it has incomparable advantages and is very suitable for the treatment of various flue gases and dusts. However, polytetrafluoroethylene, as the "king of plastics", is a completely symmetrical, unbranched linear polymer with a unique fluorine-surrounded double helix structure. This structure makes polytetrafluoroethylene difficult to process and form, has poor mechanical properties, a large expansion coefficient, poor thermal conductivity, and poor wear resistance. The dust retention and filtration performance in the dust filter bag is limited. Therefore, the existing polytetrafluoroethylene dust filter bags have defects such as low mechanical strength, poor wear resistance, and short service life, which greatly limits the use of this technology. Summary of the invention
[0004] The purpose of the present invention is to provide a polytetrafluoroethylene fiber PTFE dust removal filter bag to solve the following technical problems:
[0005] The existing polytetrafluoroethylene dust filter bag has the problems of low mechanical strength, poor wear resistance and short service life.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A polytetrafluoroethylene fiber PTFE dust filter bag, the polytetrafluoroethylene fiber PTFE dust filter bag is made by the following method:
[0008] The modified polytetrafluoroethylene fiber membrane is needle-punched on the polytetrafluoroethylene composite base cloth to obtain a polytetrafluoroethylene fiber ptfe dust removal filter bag;
[0009] Wherein, the modified polytetrafluoroethylene fiber membrane is loaded with nano-Al 2 O 3 The polytetrafluoroethylene fiber membrane of the powder, the polytetrafluoroethylene composite base fabric is glass fiber-nano SiO 2 -PTFE composite fabric.
[0010] As a further solution of the present invention: the modified polytetrafluoroethylene fiber membrane is at least arranged on the side of the polytetrafluoroethylene composite base cloth close to the dust, and the unit area weight of the polytetrafluoroethylene fiber ptfe dust filter bag is 400-800g / m 2 .
[0011] As a further solution of the present invention: the preparation method of the polytetrafluoroethylene composite base fabric comprises the following steps:
[0012] Ultrasonic mixing of tetraethyl orthosilicate and anhydrous ethanol, dropwise addition of ammonia water and deionized water, mixing evenly and reacting for 4-6 hours, then adding γ-aminopropyltriethoxysilane coupling agent and continuing the reaction for 4-6 hours to obtain an interface modifier;
[0013] The glass fiber is completely immersed in the interface modifier, left to stand, and then washed and dried to obtain the modified glass fiber;
[0014] The modified glass fiber is immersed in a polytetrafluoroethylene aqueous dispersion, and after spinning, drying, baking, sintering, cooling and weaving, a polytetrafluoroethylene composite base fabric is obtained.
[0015] As a further solution of the present invention: the ammonia water is a 25-30wt% ammonia water solution, the addition ratio of the anhydrous ethanol, the ammonia water, the deionized water, the tetraethyl orthosilicate and the γ-aminopropyltriethoxysilane coupling agent is 200mL:1-3mL:10-20mL:6-10mL:0.8-1.2mL, and the solid content of the polytetrafluoroethylene in the polytetrafluoroethylene aqueous dispersion is 40-50%.
[0016] As a further solution of the present invention: the mass ratio of the glass fiber to the interface modifier is 1:5-8, and the mass ratio of the modified glass fiber to the polytetrafluoroethylene aqueous dispersion is 1:5-10.
[0017] As a further solution of the present invention: the preparation method of the modified polytetrafluoroethylene fiber membrane comprises the following steps:
[0018] The polytetrafluoroethylene suspension is added dropwise to the polyvinyl alcohol aqueous solution, and the mixture is sealed and stirred at room temperature to obtain a spinning solution;
[0019] Nano-Al 2 O 3 The powder is added into the spinning solution, stirred and allowed to stand to obtain a modified spinning solution;
[0020] The modified spinning solution is spun, dried and sintered to obtain a modified polytetrafluoroethylene fiber membrane.
[0021] As a further solution of the present invention: the mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 10-20%, and the mass ratio of the polyvinyl alcohol to the polytetrafluoroethylene in the polytetrafluoroethylene suspension is 1:5-6.
[0022] As a further embodiment of the present invention: the nano-Al in the modified spinning solution 2 O 3 The mass fraction of powder is 0.5-1%
[0023] Beneficial effects of the present invention:
[0024] The present invention prepares the loaded nano-Al 2 O 3 Modified polytetrafluoroethylene fiber membrane and glass fiber-nano SiO 2 -polytetrafluoroethylene composite base cloth, and the modified polytetrafluoroethylene fiber membrane is compounded on the polytetrafluoroethylene based cloth through a needle punching process, and the polytetrafluoroethylene fiber ptfe dust filter bag is obtained by cutting and sewing. The polytetrafluoroethylene based cloth prepared in the present invention has excellent mechanical properties and mechanical properties, is resistant to compression and wear, and the prepared modified polytetrafluoroethylene fiber membrane enhances the hydrophobic and oil-repellent properties of polytetrafluoroethylene. The two are compounded to obtain a dust filter bag with excellent chemical stability, acid and alkali corrosion resistance, no moisture absorption, good oxidation resistance, high and low temperature resistance, good mechanical properties, anti-static, anti-condensation, tensile, compression, folding and wear resistance, and the gas filtration resistance is small, the dust removal efficiency is significant, the adaptability of the use environment is wide, the economic benefit is good, and the service life can reach more than 3 years. It can be widely used in high-temperature flue gas dust removal and filtration in steel, power generation, cement, coal-fired boilers, etc.
[0025] The present invention adopts electrostatic spinning technology to prepare polytetrafluoroethylene fiber membrane, and directly loads nano-Al with high hardness, stable crystal phase and high temperature resistance on the surface. 2 O 3The modified polytetrafluoroethylene fiber membrane is obtained by loading nano-scale Al on the surface of the polytetrafluoroethylene fiber membrane. A secondary rough structure is constructed on the fiber membrane to modify the surface of the fiber membrane and prepare a fiber membrane with excellent hydrophobic and oil-repellent properties. 2 O 3 The particles can significantly enhance the hydrophobic and oil-repellent properties of the fiber membrane while maintaining the surface morphology, and the removal efficiency of polyvinyl alcohol is good, retaining the flexibility of the film. The modified polytetrafluoroethylene fiber membrane obtained by the preparation method of the present invention can finally be compounded on a polytetrafluoroethylene-based cloth through a needle punching process, so that the obtained dust removal filter bag has the purpose of oil-proof and water-repellent, and the surface of the filter bag is not easily soaked after contact with water and oil, solving the problem of condensation and sticking of the bag, and can be used in places with high humidity. At the same time, the surface friction coefficient is small and dust is not easily adhered, so the dust layer on the surface of the filter material is easy to fall off, greatly reducing the possibility of clogging.
[0026] The invention comprises the following steps: impregnating and coating nano silicon dioxide modified by a silane coupling agent on the surface of a glass fiber, and performing surface treatment on the nano silicon dioxide by using the silane coupling agent, so as to reduce the surface energy of the nano silicon dioxide, which is beneficial for effective dispersion and adsorption of the nano silicon dioxide on the surface of the glass fiber, thereby improving the roughness of the surface of the glass fiber, and is beneficial for improving the electrostatic adsorption of the glass fiber in a polytetrafluoroethylene dispersion. After sintering and forming, the interface bonding strength between the polytetrafluoroethylene and the modified glass fiber is improved through hydrogen bonding and mechanical meshing, so as to prepare a glass fiber-nano silicon dioxide composite. 2 -Polytetrafluoroethylene composite material, after spinning and weaving, obtains polytetrafluoroethylene composite base cloth, and finally realizes the improvement of mechanical properties and mechanical properties of polytetrafluoroethylene composite base cloth. In the present invention, the glass fiber has good mechanical properties, wear resistance, dimensional stability and chemical corrosion resistance, and nano silicon dioxide has flame retardancy and wear resistance. Using glass fiber and silicon dioxide as fillers can improve the hardness and compressive strength of the composite material, reduce shrinkage, wear and production cost. The base cloth obtained by the present invention does not decompose at high temperature, does not crack at low temperature, basically will not deform or lack rolls after bearing compression load, has excellent dimensional stability, almost no elongation, excellent wear resistance and flame retardancy, which greatly extends the service life of the dust filter bag. DETAILED DESCRIPTION
[0027] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Embodiment 1 The preparation method of modified polytetrafluoroethylene fiber membrane comprises the following steps:
[0029] Weigh 5 g of polyvinyl alcohol particles and dissolve them in 45 g of deionized water. After standing and degassing, a transparent polyvinyl alcohol solution with a mass fraction of 10% is obtained. Then, a polytetrafluoroethylene suspension containing 30 g of polytetrafluoroethylene is slowly added dropwise to the polyvinyl alcohol solution, and the solution is sealed and stirred at room temperature for 4 hours to form a spinning solution with a polytetrafluoroethylene / polyvinyl alcohol mass ratio of 6:1;
[0030] Weigh 0.5% of nano-Al 2 O 3 The powder was poured into the spinning solution, stirred with a magnetic stirrer for 4 hours, and allowed to stand for 12 hours to degas after the stirring was completed, to obtain a modified spinning solution;
[0031] The modified spinning solution was spun at room temperature, and the parameters were set as follows: voltage (-2, +17) kV, injection speed 0.6 mL / h, receiving distance between the nozzle and the spinning receiving roller 15 cm, roller speed 600 r / min, and then dried in a drying oven at 60°C for 4 h, and then placed in a muffle furnace for sintering at 330°C to obtain a modified polytetrafluoroethylene fiber membrane.
[0032] Embodiment 2 The preparation method of the modified polytetrafluoroethylene fiber membrane comprises the following steps:
[0033] Weigh 5 g of polyvinyl alcohol particles and dissolve them in 45 g of deionized water. After standing and degassing, a transparent polyvinyl alcohol solution with a mass fraction of 10% is obtained. Then, a polytetrafluoroethylene suspension containing 30 g of polytetrafluoroethylene is slowly added dropwise to the polyvinyl alcohol solution, and the solution is sealed and stirred at room temperature for 4 hours to form a spinning solution with a polytetrafluoroethylene / polyvinyl alcohol mass ratio of 6:1;
[0034] Weigh 0.8% of nano-Al 2 O 3 The powder was poured into the spinning solution, stirred with a magnetic stirrer for 4 hours, and allowed to stand for 12 hours to degas after the stirring was completed, to obtain a modified spinning solution;
[0035] The modified spinning solution was spun at room temperature, and the parameters were set as follows: voltage (-2, +17) kV, injection speed 0.6 mL / h, receiving distance between the nozzle and the spinning receiving roller 15 cm, roller speed 600 r / min, and then dried in a drying oven at 60°C for 4 h, and then placed in a muffle furnace for sintering at 330°C to obtain a modified polytetrafluoroethylene fiber membrane.
[0036] Embodiment 3 The preparation method of polytetrafluoroethylene composite base fabric comprises the following steps:
[0037] First, 6.0 mL of tetraethyl orthosilicate and 200 mL of anhydrous ethanol were ultrasonically mixed, and then 2.0 mL of ammonia water and 20 mL of deionized water were added thereto, and after being mixed evenly, the mixture was placed in a water bath at 40° C. to react for 5 h, and then 0.8 mL of γ-aminopropyltriethoxysilane coupling agent was added and reacted at 60° C. to obtain an interface modifier containing amino-silica.
[0038] 30 g of glass fiber is placed in deionized water at 90° C., and after standing for a period of time, it is taken out and then placed in an α-amylase treatment solution, and placed in a constant temperature and humidity chamber, and after being kept for 2 hours, it is taken out, and repeatedly washed three times, and dried to constant weight to obtain the glass fiber after removing the wetting agent, and the glass fiber after removing the wetting agent is completely immersed in the above-mentioned interface modifier, and stood for 4 hours. After being taken out, it is washed with anhydrous ethanol and deionized water respectively, and dried to obtain a modified glass fiber;
[0039] The modified glass fiber is immersed in 200 mL of a polytetrafluoroethylene aqueous dispersion having a solid content of 40% polytetrafluoroethylene, dried at 150° C. and baked at 280° C. for multiple cycles, sintered at high temperature, and rapidly cooled to obtain a polytetrafluoroethylene composite material;
[0040] The polytetrafluoroethylene composite material is subjected to extrusion, calendering, stretching, heating stretching, heating stretching, slitting, twisting into bundles, rough extrusion stretching, fine extrusion stretching, heating stretching, and curling, and then prepared according to the warp and weft yarn process to obtain a polytetrafluoroethylene composite base cloth with a thickness of 0.45±0.05mm.
[0041] Embodiment 4 The preparation method of polytetrafluoroethylene composite base fabric comprises the following steps:
[0042] First, 6.0 mL of tetraethyl orthosilicate and 200 mL of anhydrous ethanol were ultrasonically mixed, and then 2.0 mL of ammonia water and 20 mL of deionized water were added thereto, and after being mixed evenly, the mixture was placed in a water bath at 40° C. to react for 5 h, and then 0.8 mL of γ-aminopropyltriethoxysilane coupling agent was added and reacted at 60° C. to obtain an interface modifier containing amino-silica.
[0043] The glass fiber is placed in deionized water at 90°C, and after standing for a period of time, the GFF is taken out and put into the α-amylase treatment solution again, and then taken out and placed in a constant temperature and humidity box, and the fabric is taken out after being kept for a certain period of time, and repeatedly washed three times, and finally dried to constant weight to obtain the glass fiber after removing the impregnant, and the above GFF-T is completely immersed in the above interfacial modifier, and stood for a period of time, and then taken out and washed with anhydrous ethanol and deionized water respectively, and dried to obtain the modified glass fiber;
[0044] 35 g of glass fiber is placed in deionized water at 90° C., and after standing for a period of time, it is taken out and then placed in an α-amylase treatment solution, and placed in a constant temperature and humidity chamber, and after being kept for 2 hours, it is taken out, and repeatedly washed three times, and dried to constant weight to obtain the glass fiber after removing the wetting agent, and the glass fiber after removing the wetting agent is completely immersed in the above-mentioned interface modifier, and stood for 4 hours. After being taken out, it is washed with anhydrous ethanol and deionized water respectively, and dried to obtain a modified glass fiber;
[0045] The modified glass fiber is immersed in 200 mL of a polytetrafluoroethylene aqueous dispersion having a solid content of 40% polytetrafluoroethylene, dried at 150° C. and baked at 280° C. for multiple cycles, sintered at high temperature, and rapidly cooled to obtain a polytetrafluoroethylene composite material;
[0046] The polytetrafluoroethylene composite material is subjected to extrusion, calendering, stretching, heating stretching, heating stretching, slitting, twisting into bundles, rough extrusion stretching, fine extrusion stretching, heating stretching, and curling, and then prepared according to the warp and weft yarn process to obtain a polytetrafluoroethylene composite base cloth with a thickness of 0.45±0.05mm.
[0047] Embodiment 5 A polytetrafluoroethylene fiber ptfe dust removal filter bag is made by the following method:
[0048] The modified polytetrafluoroethylene fiber membrane prepared in Example 1 is laid on both sides of the polytetrafluoroethylene composite base fabric prepared in Example 3, and the laying thickness of the modified polytetrafluoroethylene fiber membrane is 1 mm. Then, the modified polytetrafluoroethylene fiber membrane and the polytetrafluoroethylene composite base fabric are compounded by a needle punching process, and the needle punching density is 400-600 thorns / cm 2 After cutting and sewing, the polytetrafluoroethylene fiber ptfe dust filter bag is obtained.
[0049] Embodiment 6 A polytetrafluoroethylene fiber PTFE dust removal filter bag is made by the following method:
[0050] The modified polytetrafluoroethylene fiber membrane prepared in Example 1 is laid on both sides of the polytetrafluoroethylene composite base fabric prepared in Example 4, and the laying thickness of the modified polytetrafluoroethylene fiber membrane is 1 mm. Then, the modified polytetrafluoroethylene fiber membrane and the polytetrafluoroethylene composite base fabric are compounded by a needle punching process, and the needle punching density is 400-600 thorns / cm 2 After cutting and sewing, the polytetrafluoroethylene fiber ptfe dust filter bag is obtained.
[0051] Embodiment 7 A polytetrafluoroethylene fiber PTFE dust removal filter bag is made by the following method:
[0052] The modified polytetrafluoroethylene fiber membrane prepared in Example 2 is laid on both sides of the polytetrafluoroethylene composite base fabric prepared in Example 3, and the laying thickness of the modified polytetrafluoroethylene fiber membrane is 1 mm. Then, the modified polytetrafluoroethylene fiber membrane and the polytetrafluoroethylene composite base fabric are compounded by a needle punching process, and the needle punching density is 400-600 thorns / cm 2 After cutting and sewing, the polytetrafluoroethylene fiber ptfe dust filter bag is obtained.
[0053] Embodiment 8 A polytetrafluoroethylene fiber PTFE dust removal filter bag is made by the following method:
[0054] The modified polytetrafluoroethylene fiber membrane prepared in Example 2 was laid on both sides of the polytetrafluoroethylene composite base fabric prepared in Example 4, and the laying thickness of the modified polytetrafluoroethylene fiber membrane was 1 mm. Then, the modified polytetrafluoroethylene fiber membrane and the polytetrafluoroethylene composite base fabric were compounded by a needle punching process, and the needle punching density was 400-600 thorns / cm 2 After cutting and sewing, the polytetrafluoroethylene fiber ptfe dust filter bag is obtained.
[0055] Comparative Example 1 A polytetrafluoroethylene fiber PTFE dust removal filter bag is made by the following method:
[0056] The preparation step of the polytetrafluoroethylene composite base cloth is omitted, and the modified polytetrafluoroethylene fiber membrane prepared in Example 1 is laid on both sides of the commercially available glass fiber base cloth, and the laying thickness of the modified polytetrafluoroethylene fiber membrane is 1 mm. Then, the modified polytetrafluoroethylene fiber membrane and the polytetrafluoroethylene composite base cloth are compounded by a needle punching process, and the needle punching density is 400-600 thorns / cm 2 After cutting and sewing, the polytetrafluoroethylene fiber ptfe dust filter bag is obtained.
[0057] Comparative Example 2 A polytetrafluoroethylene fiber PTFE dust removal filter bag is made by the following method:
[0058] The step of preparing the modified polytetrafluoroethylene fiber membrane is omitted, and the polytetrafluoroethylene composite base cloth prepared in Example 3 is cut and sewn to obtain a polytetrafluoroethylene fiber PTFE dust removal filter bag.
[0059] Comparative Example 3 The preparation method of polytetrafluoroethylene composite base fabric comprises the following steps:
[0060] 30g of glass fiber is immersed in 200mL of polytetrafluoroethylene aqueous dispersion with a solid content of 40% polytetrafluoroethylene, dried at 150°C and baked at 280°C, and after multiple cycles, sintered at high temperature and rapidly cooled to obtain a polytetrafluoroethylene composite material;
[0061] The polytetrafluoroethylene composite material is subjected to extrusion, calendering, stretching, heating stretching, heating stretching, slitting, twisting into bundles, rough extrusion stretching, fine extrusion stretching, heating stretching, and curling, and then prepared according to the warp and weft yarn process to obtain a polytetrafluoroethylene composite base cloth.
[0062] A polytetrafluoroethylene fiber ptfe dust removal filter bag is made by the following method:
[0063] The modified polytetrafluoroethylene fiber membrane prepared in Example 1 was laid on both sides of the polytetrafluoroethylene composite base fabric prepared in this comparative example, and the laying thickness of the modified polytetrafluoroethylene fiber membrane was 1 mm. Then, the modified polytetrafluoroethylene fiber membrane and the polytetrafluoroethylene composite base fabric were compounded by a needle punching process, and the needle punching density was 400-600 thorns / cm 2 After cutting and sewing, the polytetrafluoroethylene fiber ptfe dust filter bag is obtained.
[0064] Comparative Example 4 A polytetrafluoroethylene fiber ptfe dust removal filter bag is made by the following method:
[0065] The modified polytetrafluoroethylene fiber membrane prepared in Example 1 was laid on both sides of the commercially available polytetrafluoroethylene based cloth, and the laying thickness of the modified polytetrafluoroethylene fiber membrane was 1 mm. Then, the modified polytetrafluoroethylene fiber membrane and the polytetrafluoroethylene composite base cloth were compounded by a needle punching process, and the needle punching density was 400-600 thorns / cm 2 After cutting and sewing, the polytetrafluoroethylene fiber ptfe dust filter bag is obtained.
[0066] Performance Testing
[0067] Contact angle: The static contact angles of the polytetrafluoroethylene fiber ptfe dust removal filter bags obtained in Examples 5-8 and Comparative Examples 1-4 were measured using a DSA30 contact angle meter produced by Kruess, Germany. The test results are shown in Table 1;
[0068] Flame retardancy: According to GB / T14656-2009 standard, vertical combustion tests were performed on the polytetrafluoroethylene fiber ptfe dust filter bags obtained in Examples 5-8 and Comparative Examples 1-4, and the test results are shown in Table 1;
[0069] Friction resistance: According to GB / 3960-83 standard, the polytetrafluoroethylene fiber ptfe dust filter bags obtained in Examples 5-8 and Comparative Examples 1-4 were tested on a MM-200 friction and wear tester to determine the friction and wear properties of the composite materials. The test results are shown in Table 1.
[0070] Filtration efficiency: According to HJ / T324-2006 standard, the filtration efficiency and service life of the polytetrafluoroethylene fiber ptfe dust removal filter bags obtained in Examples 5-8 and Comparative Examples 1-4 were tested respectively. The test results are shown in Table 1;
[0071] Mechanical properties: According to GB / T 7689.5 standard, the mechanical properties of the polytetrafluoroethylene fiber ptfe dust filter bags obtained in Examples 5-8 and Comparative Examples 1-4 were tested using an Instron-3369 universal testing machine. The test results are shown in Table 1.
[0072] Table 1: Statistical table of dust filter bag performance test data for Examples 5-8 and Comparative Examples 1-4
[0073]
[0074]
[0075] It can be seen from Table 1 that the polytetrafluoroethylene fiber PTFE dust removal filter bags prepared in Examples 5-8 of the present invention and Comparative Examples 1-4 have good hydrophobicity and oil repellency, flame retardancy and friction resistance, good mechanical properties, long service life, and significant dust removal efficiency. The dust removal efficiency can be as high as 99%, which greatly exceeds the national standard and is close to zero emissions. In Comparative Example 1, modified polytetrafluoroethylene fibers are needle-punched on both sides of a commercially available glass fiber base cloth, and a dust filter bag is formed by cutting and sewing. The friction resistance and mechanical properties of the obtained dust filter bag are reduced, and the filtration efficiency and service life are also greatly reduced. In Comparative Example 2, the polytetrafluoroethylene composite base cloth is directly cut and sewn to form a dust filter bag. The hydrophobicity and friction resistance of the obtained dust filter bag are reduced, and the dust removal efficiency is also reduced. In Comparative Example 3, the glass fiber is not modified, and the flame retardant properties of the obtained dust filter bag are poor, and the mechanical properties are also reduced. In Comparative Example 4, modified polytetrafluoroethylene fibers are needle-punched on both sides of a commercially available polytetrafluoroethylene base cloth, and a dust filter bag is formed by cutting and sewing. The friction resistance, flame retardant properties and mechanical properties of the obtained dust filter bag are greatly reduced.
[0076] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A polytetrafluoroethylene fiber ptfe dust removal filter bag, characterized in that: The polytetrafluoroethylene fiber ptfe dust removal filter bag is made by the following method: The modified polytetrafluoroethylene fiber membrane is needle-punched on the polytetrafluoroethylene composite base cloth to obtain a polytetrafluoroethylene fiber PTFE dust removal filter bag; Wherein, the modified polytetrafluoroethylene fiber membrane is a polytetrafluoroethylene fiber membrane loaded with nano-Al2O3 powder, and the polytetrafluoroethylene composite base cloth is a glass fiber-nano-SiO2-polytetrafluoroethylene composite base cloth.
2. A polytetrafluoroethylene fiber ptfe dust removal filter bag according to claim 1, characterized in that: The modified polytetrafluoroethylene fiber membrane is at least arranged on the side of the polytetrafluoroethylene composite base cloth close to the dust, and the unit area weight of the polytetrafluoroethylene fiber ptfe dust removal filter bag is 400-800g / m 2 .
3. A polytetrafluoroethylene fiber ptfe dust removal filter bag according to claim 1, characterized in that: The preparation method of the polytetrafluoroethylene composite base fabric comprises the following steps: Ultrasonic mixing of tetraethyl orthosilicate and anhydrous ethanol, dropwise addition of ammonia water and deionized water, mixing evenly and reacting for 4-6 hours, then adding γ-aminopropyltriethoxysilane coupling agent and continuing the reaction for 4-6 hours to obtain an interface modifier; The glass fiber is completely immersed in the interface modifier, left to stand, and then washed and dried to obtain the modified glass fiber; The modified glass fiber is immersed in a polytetrafluoroethylene aqueous dispersion, and after spinning, drying, baking, sintering, cooling and weaving, a polytetrafluoroethylene composite base fabric is obtained.
4. A polytetrafluoroethylene fiber ptfe dust removal filter bag according to claim 3, characterized in that: The ammonia water is a 25-30wt% ammonia water solution, the addition ratio of the anhydrous ethanol, the ammonia water, the deionized water, the tetraethyl orthosilicate and the γ-aminopropyltriethoxysilane coupling agent is 200mL:1-3mL:10-20mL:6-10mL:0.8-1.2mL, and the solid content of the polytetrafluoroethylene in the polytetrafluoroethylene aqueous dispersion is 40-50%.
5. A polytetrafluoroethylene fiber ptfe dust removal filter bag according to claim 3, characterized in that: The mass ratio of the glass fiber to the interface modifier is 1:5-8, and the mass ratio of the modified glass fiber to the polytetrafluoroethylene aqueous dispersion is 1:5-10.
6. A polytetrafluoroethylene fiber ptfe dust removal filter bag according to claim 1, characterized in that: The preparation method of the modified polytetrafluoroethylene fiber membrane comprises the following steps: The polytetrafluoroethylene suspension is added dropwise to the polyvinyl alcohol aqueous solution, and the mixture is sealed and stirred at room temperature to obtain a spinning solution; Adding nano-Al2O3 powder into the spinning solution, stirring and standing to obtain a modified spinning solution; The modified spinning solution is spun, dried and sintered to obtain a modified polytetrafluoroethylene fiber membrane.
7. A polytetrafluoroethylene fiber ptfe dust removal filter bag according to claim 6, characterized in that: The mass fraction of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 10-20%, and the mass ratio of the polyvinyl alcohol to the polytetrafluoroethylene in the polytetrafluoroethylene suspension is 1:5-6.
8. A polytetrafluoroethylene fiber ptfe dust removal filter bag according to claim 6, characterized in that: The mass fraction of the nano-Al2O3 powder in the modified spinning solution is 0.5-1%.
Citation Information
Patent Citations
Production process for polytetrafluoroethylene (PTFE) aqua tex composite high-temperature tail gas filter material
CN102527156A
Modified PTFE (polytetrafluoroethylene) fiberglass cloth for copper-clad plates and preparation method of fiberglass cloth
CN105904806A
Improved wear polytetrafluoroethylene (PTFE) fiber and method of making same
CN109913969A
Preparation method for improving temperature resistance of alkali-free glass fiber woven fabric filter material
CN113320236A
Preparation method of multilayer polytetrafluoroethylene hollow fiber membrane
CN113680217A